Pro C# 9 with . NET 5 foundational principles and practices in programming - Troelsen, Andrew (Apress L.P., 2021)
This essential classic provides a comprehensive foundation in the C# programming language and the framework it lives in. Now in its 10th edition, you will find the latest C# 9 and .NET 5 features served up with plenty of "behind the curtain" discussion designed to expand developers' critical thinking skills when it comes to their craft. Coverage of ASP.NET Core, Entity Framework Core, and more, sits alongside the latest updates to the new unified .NET platform, from performance improvements to Windows Desktop apps on .NET 5, updates in XAML tooling, and expanded coverage of data files and data handling. Going beyond the latest features in C# 9, all code samples are rewritten for this latest release. Dive in and discover why this book is a favorite of C# developers worldwide. Gain a solid foundation in object-oriented development techniques, attributes and reflection, generics and collections, and numerous advanced topics not found in other texts (such as CIL opcodes and emitting dynamic assemblies). With the help of Pro C# 9 with .NET 5 you will gain the confidence to put C# into practice, and explore the .NET universe and its vast potential on your own terms
Print version record. - Online resource; title from PDF title page (SpringerLink, viewed May 4, 2021)
Keywords: Microsoft .NET Framework; C# (Computer program language); Application software -- Development; Internet programming; C# (Langage de programmation); Logiciels d'application; Développement; Programmation Internet; Application software; Development